PERLINDUNGAN RAHASIA DAGANG DALAM PERSPEKTIF HUKUM DI INDONESIA (Studi Kasus Pembocoran Rahasia Dagang Racikan Kopi CV Bintang Harapan) - Hikmah, Faidatul; Yanto, Andri (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2022)
Trade secrets are important economic commodities and require effective protection by the state. The existence of trade secrets is closely related to product sales value, business continuity, and fair competition among competing products. As a rule-of-law country that guarantees freedom of business, Indonesia has prepared various instruments to guarantee the protection of trade secrets. By using a juridical-normative analysis approach, this study focuses on efforts to find out the form of trade law protection in Indonesia, with a comparison of the trade secret leaks of CV Bintang Harapan. Trade secret protection in Indonesia is provided through preventive and curative efforts. The state is present to record trade secret registration and make countermeasures to complaints offences However, the low level of public awareness of business owners to register their trade secrets is still an obstacle because proving the disclosure of trade secrets can be difficult. In addition, the delict nature of the complaint also limits the government's efforts to directly follow up on trade secret violations